Measuring the Knowledge Base of Regional Innovation Systems in Germany in terms of a Triple Helix Dynamics - Loet Leydesdorff; Michael Fritsch (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2005)
While a market economy seeks equilibrium, a knowledge-based economy may upset this tendency towards stabilization by adding the feedback of globalization. The interaction among the three subdynamics of economic exchange, technological innovation, and institutional control can be captured with a generalized Triple Helix model. We propose to use the mutual information as an indicator of integration among the three subdynamics at the systems level. This probabilistic entropy can be positive or negative. On the basis of data at the district level in Germany the conclusions of a previous study about the Netherlands are tested: medium-tech manufacturing is the main driver of a knowledge-based configuration in a regional economy, while knowledge-intensive services tend to uncouple the economy from the regional configuration. At the level of regions (NUTS-2) the knowledge-based economy is no longer structured by the previous East-West divide of the country, while this divide has remained the main structure at the level of the states (NUTS-1) which constitute the Federal Republic. – – Während eine Marktwirtschaft nach Gleichgewicht strebt, kann diese Stabilisierungs-tendenz in einer Wissensgesellschaft durch einen zusätzlichen Feedback-Effekt der Globalisierung gestört werden. Das Zusammenspiel der drei Teildynamiken ökonomi-scher Austausch, technologische Innovation und institutionelle Kontrolle kann mit ei-nem allgemeinen Triple Helix-Model erfasst werden. Wir nutzen die gegenseitigen Informationsflüsse zwischen diesen drei Teildynamiken als einen Indikator für die systemische Integration dieser drei Bereiche. Dies probabilistische Entropy kann positiv oder negativ sein. Wir untersuchen, ob Ergebnisse einer früheren, für die Niederlande durchgeführten Studie auch auf Deutschland zutreffen. Wie in den Niederlanden erweist sich auch in Deutschland die medium-tech Industrie als wesentliche Triebkraft der regionalen Wissensbasis während die wissensintensiven Dienstleistungen offenbar weitgehend losgelöst von regionalen Gegebenheiten sind. Während auf der Ebene von Bundesländern (NUTS-1 Regionen) noch ein klarer Ost-West-Unterschied festgestellt werden kann ist das Bild auf der feineren Ebene von NUTS-2 Regionen wesentlich differenzierter.
Keywords: O18; R12; O31; C14; 330; Wissensgesellschaft; Triple Helix; Regionale Innovationssysteme; Deutschland; Probabilistische Entropy; Knowledge economy; Triple Helix; regional innovation systems; Germany; probabilistic entropy; Informationsgesellschaft; Innovation; Wissen; Region; Entropie; Niederlande; Deutschland